Integrasi Konsep Fitrah dan Teori Tabula Rasa dalam Kurikulum Pendidikan Anak Usia Dini - Ngatmin Abbas (Iftitiah: Jurnal Ilmiah Pendidikan Islam Anak Usia Dini, 2024)
Early childhood education is a critical phase in the development of a child's character, morals, and intellect. This research aims to integrate the concept of fitrah, which emphasizes that children are born with innate potential, with the tabula rasa theory, which states that children are blank slates shaped by experience. This study uses a qualitative method with a library research approach, analyzing literature related to both concepts and their relevance to early childhood education. The findings reveal that integrating fitrah and tabula rasa can aid in designing a holistic curriculum, one that develops not only children's academic intelligence but also their moral and social values. Moreover, this approach encourages parental and environmental involvement in the educational process, creating a supportive environment for optimal child development. Therefore, the integration of these two concepts provides a more balanced framework for educating an intelligent and well-characterized generation.